ICT in Chilean schools: Students’ and teachers’ access and use of ICT - Hinostroza, Enrique; Labbé, Christian; Claro, Magdalena (Human Technology, 2005)
This paper presents the results of the analysis of the data from a national survey of the Chilean educational ICT infrastructure and its use in schools implemented by the Centre for Technology and Education of the Chilean Ministry of Education in 2004. Results show that the context of ICT use in Chilean schools can be characterized as relatively good, insofar as there are no first-order barriers for implementing ICT pedagogy. In this context, students’ ICT use can be categorized based on four factors: communication, productivity, recreation, and communication with teachers. On the other hand, teachers’ ICT use can be categorized using three factors: communication, teaching, and technical. Based on these factors and considering the availability and use of ICT in schools, the question remains how to make this time most effective for improving students’ learning. Additionally, results show that students, on their own, spend a considerable amount of time developing activities described as communication. The question that arises from this finding is how to take advantage of these activities in order to meet teaching and learning aims. Regarding teachers, results open possibilities for redesigning professional development courses by taking advantage of what they already do with ICT.